Narrative Analysis in Bayer Leverkusen’s Journey to Champion Youtube Review Video - Rahayu, Dwi; Akbar, Muhammad Zikri; Dzaki, Muhammad Haekal; Hidayah, Lutfiana Zalfa (Universitas Pamulang, 2024)
This study aims to recognize the types of narratives contained in a video that tells the story of Bayer 04 Leverkusen's journey in winning the Bundesliga title for the 2023/2024 season. The video was published through the Bundesliga's official channel on YouTube with the title